Disparate SAR data of Griseofulvin analogues for the dermatophytes trichophyton mentagrophytes, T. rubrum, and MDA-MB-231 cancer cells - Rønnest, Mads H.; Raab, Marc-Steffen; Anderhub, Simon; Krämer, Alwin (Journal of medicinal chemistry, 2012)
Griseofulvin and 53 analogues of this compound have been tested against the pathogenic dermatophytes Trichophyton rubrum and Trichophyton mentagrophytes as well as against the breast cancer cell line MDA-MB-231. The modifications to griseofulvin include the 4, 5, 6, 2′, 3′, and 4′ positions. The SAR of the griseofulvin analogues toward the two fungi followed the same trend with the majority being less active than griseofulvin and none had more than twice the potency of the parent compound. A comparison of the antifungal and the anticancer SAR revealed distinct differences, as the majority of analogues showed increased activity against the cancer cell line MDA-MB-231, highlighted by 2′-benzyloxy-2′-demethoxy-griseofulvin, which showed low activity against both fungi but was among the most potent compounds against MDA-MB-231 cancer cells. Tubulin has been proposed as the target of griseofulvin in both fungal and mammalian cells, but the differences revealed by this SAR study strongly suggest that the mode-of-action of the compound class toward fungi and mammalian cancer cells is different.